2020
DOI: 10.1016/j.engstruct.2020.110297
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of parameters influencing fire evaluation tests of chemically bonded anchors in uncracked concrete

Abstract: European guidelines for fire performance evaluation of post-installed anchoring systems are limited to mechanical (e.g., expansive, undercut) mechanisms of load transfer and the steel failure mode, whereas the adhesive bond mechanism remains unaccounted for in chemically bonded anchors. Furthermore, current evaluation methods do not account for the influence of practical testing conditions on temperature profiles along the bonded depth. This paper presents 3D finite element thermal simulations of chemically bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 18 publications
0
15
0
1
Order By: Relevance
“…Standard metallic fixtures for such fire tests were used [ 16 ]. The influence of the loading systems on temperature profiles and resulting pull-out capacity of bonded anchors in the heating phase were investigated by [ 10 , 11 ] and found negligible. The steel of the loading system was insulated using a ceramic wool-based material to protect the steel from reaching failure and to induce a pull-out (bond) failure.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…Standard metallic fixtures for such fire tests were used [ 16 ]. The influence of the loading systems on temperature profiles and resulting pull-out capacity of bonded anchors in the heating phase were investigated by [ 10 , 11 ] and found negligible. The steel of the loading system was insulated using a ceramic wool-based material to protect the steel from reaching failure and to induce a pull-out (bond) failure.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
“…The 3D model considers the PIR as a perfect cylinder inside the concrete beam with an embedment depth of 160 mm of the steel inside the concrete, and 40 mm of extended length ( Figure 4 ). Al Mansouri et al [ 11 ] conducted a parametric study to investigate the influence of the extended length of the steel above the concrete surface and concluded that this external length influences temperature profiles between no extended length and 20 mm of extended length. Beyond 20 mm from the concrete surface, the influence is insignificant for a medium size anchor (M12).…”
Section: 3d Transient Thermal Analysis Using Ansysmentioning
confidence: 99%
See 2 more Smart Citations
“…The results were used as a basis for numerical simulations, using a shear lag model considering bond stress and displacement compatibility along the anchor [46]. Al-Mansouri et al used numerical simulations [47] and experimental tests [48] to investigate test parameters influencing the evaluated fire resistance.…”
Section: Research Closing the Gapmentioning
confidence: 99%